Biohydrogen production in a continuous stirred tank bioreactor from synthesis gas by anaerobic photosynthetic bacterium: Rhodopirillum rubrum - Younesi, Habibollah; Najafpour, Ghasem D.; Ku Syahidah, Ku Ismail; Abdul Rahman, Mohamed; Azlina, Harun Kamaruddin (Elsevier Ltd., 2009)
Link to publisher's homepage at www.elsevier.com